2021
DOI: 10.2174/1568026621666210331152702
|View full text |Cite
|
Sign up to set email alerts
|

Cruzain and Rhodesain Inhibitors: Last Decade of Advances in Seeking for New Compounds Against American and African Trypanosomiases

Abstract: : Neglected tropical diseases (NTDs) are a group of approximately 20 diseases that affect part of the population in Sub- and Tropical countries. In the past, pharmaceutical industries and governmental agencies have invested in the control, elimination and eradication of such diseases. Among these diseases, Chagas disease (CD) and Human African trypanosomiasis (HAT) are a public health problem, mainly in the countries from the American continent and sub-Saharan African. In this context, the search for new thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The ligands showed a fit score between 49.85 -94.18 (Table 1), and a covalent fit score varying between 49.91 -141.52 (Table 1). In addition, it was observed that the compounds with conventional fit score and covalent fit score better than 55 and 90, respectively, showed interactions with the main residues related to the cruzain inhibition (Cys 25 , His 159 , Glu 23 , Gly 65 , and Glu 205 ) [3,5,6,26,27] (Table 1). Other works used a similar protocol to search new hits to drug design [10,28,29].…”
Section: Screening Protocol Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…The ligands showed a fit score between 49.85 -94.18 (Table 1), and a covalent fit score varying between 49.91 -141.52 (Table 1). In addition, it was observed that the compounds with conventional fit score and covalent fit score better than 55 and 90, respectively, showed interactions with the main residues related to the cruzain inhibition (Cys 25 , His 159 , Glu 23 , Gly 65 , and Glu 205 ) [3,5,6,26,27] (Table 1). Other works used a similar protocol to search new hits to drug design [10,28,29].…”
Section: Screening Protocol Validationmentioning
confidence: 99%
“…With PDB crystal structure, GOLD ® algorithm selected and the start point values for screening the drugs, the next stage was built the ligand dataset. For this, 1615 FDA-approved drugs from the ZINC database were visually analyzed for choosing the drugs with chemical groups that can interact covalently with the sulfur atom of Cys 25 from cruzain [3]. This analysis resulted in the selection of 241 drugs that contained ester, carbon α-halogenated, nitrile, amide, and alkenes, and alkyne.…”
Section: Screening Protocol Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…cruzi . Moreover, it is recognized by the host as an antigen and modulates the host macrophage response. , Tbr CATL is important for penetration through the blood–brain barrier and is essential for parasite survival. ,, Efforts to develop inhibitors have led to the discovery of many potent chemotypes against both proteases (reviewed in refs , , and ). Recently reported inhibitors include peptidomimetics and nonpeptidic small molecules that inhibit the enzymes irreversibly or reversibly. In addition to their efficacy in in vitro assays against trypanosomes, ,,, cysteine protease inhibitors have shown efficacy in mice and dog models of Chagas disease, and to reduce parasitemia and/or increase survival ,, in mouse models of T.…”
Section: Introductionmentioning
confidence: 99%